First Trimester Rupture of Scarred Uterus After Use of Mifepristone, Misoprostol A-Case Report. - Begum, Fatema; Akhter, Sheuly; Shakil, Shariful Islam (KYAMC Journal, 2019)
Uterine rupture is a disastrous obstetric complication, occurring mostly in second and third trimesters. The risk of uterine rupture markedly increases with previous uterine surgeries. Termination of early pregnancy failure by misoprostol is common. However, its use in women with scarred uterus is speculative and usually puts the obstetricians in a stressful condition. Here we present a case of rupture of a scared uterus in the first trimester after using mifepristone and misoprostol. A 25 years old parous lady presented with uterine rupture after taking mifepristone and misoprostol by herself to induce abortion for unwanted pregnancy. Immediate laparotomy was done and the defect was repaired. Termination of pregnancy in a woman with scarred uterus by mifepristone and misoprostol can lead to uterine rupture. It should be used cautiously under close supervision or other routes (vaginal or oral). KYAMC Journal Vol. 10, No.-1, April 2019, Page 57-59